Physico-chemical study of sulfonated poly(ether ether ketone) membranes for direct methanol fuel cell application - Othman, M. H. D.; Ismail, A. F.; Mustafa, A. (Plastics and Rubber Institute of Malaysia, 2007)
Sulfonated poly(ether ether ketone) (SPEEK) membranes have been prepared as a potential polymer electrolyte membrane (PEM) for direct methanol fuel cell (DMFC) application. The SPEEK polymer was dissolved into N, N-dimethylacetamide (DMAc) in a subsequent step after sulfonating the raw polymer with concentrated sulfuric acid. The polymer solutions were then cast by pneumatic casting machine. The influence of sulfonation reaction temperature on ion exchange capacity (IEC) and degree of sulfonation (DS) havebeen investigated. The results showed that the IEC and DS are increased with the temperature. The resulting membranes were then characterized by evaluating their physicochemicalproperties such as methanol permeability and proton conductivity as a function of DS. The overall results showed that sulfonation process successfully enhanced the protonconductivity of the membrane and the values were comparable with commercial membrane, NafionÂ® 117, at room temperature. Although the methanol permeability of membrane alsoincreased after sulfonation process and proportional with DS, the value was still lower than NafionÂ® 117.